2018
DOI: 10.1016/j.ijscr.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic neuroectodermal tumour of infancy: A report of two cases

Abstract: HighlightsShedding light on the aggressive nature and rare incidence of Melanotic Neuroectodermal Tumour of Infancy (MNTI).Detailing different clinical and radiographic features of MNTI.Outlining the management of MNTI and postoperative follow-up regimen.Emphasising the importance of early diagnosis and surgical intervention in Melanotic Neuroectodermal Tumour of Infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…Radiographic examination is useful in determining the surgical design. 10,16,17 Histologically, the H&E stained specimen showed a biphasic population of cells forming nests, tubules, or alveolar structures within a fibro cellular connective stroma. The alveolar and tubular structures are lined by a cuboidal epithelioid cell with granules of melanin pigment.…”
Section: Discussionmentioning
confidence: 99%
“…(2) DISCUSSION OF MANAGEMENT Management of newly born haemangioma involved a wide range of treatment options starting from observation for spontaneous regression of the lesion and conservative propranolol treatment to surgical intervention with either conventional resection or with adjunctive laser therapy. (7,10) Immediately, the decision was taken to remove the lesion entirely under local anaesthesia, after performing full clinical examination, ultrasound, fine needle aspiration biopsy, (Fig. 2) and obtaining the consent of the patient's parents.…”
Section: Differential Diagnosismentioning
confidence: 99%